2011
DOI: 10.1074/jbc.m111.255984
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin-4 and CLP36 Protein Deficiencies Contribute to Podocyte Defects in Multiple Human Glomerulopathies

Abstract: Genetic alterations of ␣-actinin-4 can cause podocyte injury through multiple mechanisms. Although a mechanism involving gain-of-␣-actinin-4 function was well described and is responsible for a dominantly inherited form of human focal segmental glomerulosclerosis (FSGS), evidence supporting mechanisms involving loss-of-␣-actinin-4 function in human glomerular diseases remains elusive. Here we show that ␣-actinin-4 deficiency occurs in multiple human primary glomerulopathies including sporadic FSGS, minimal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Mutations in podocyte genes that regulate the slit diaphragm, cell membrane, and cytoskeleton are increasingly recognized, not only in FSGS but in other forms of GN as well. 224 African Americans with nondiabetic nephropathy express variants in the gene encoding APOL1. [225][226][227][228][229] Both clinical and experimental studies document the importance of several other genes, especially ones that regulate the podocyte actin cytoskeleton, in modulating the development of proteinuria, foot process effacement, and sclerosis, including RhoA, urokinase receptor, Pdlim2, and connective tissue growth factor.…”
Section: Diseases That Usually Present With Nephrotic Syndromementioning
confidence: 99%
“…Mutations in podocyte genes that regulate the slit diaphragm, cell membrane, and cytoskeleton are increasingly recognized, not only in FSGS but in other forms of GN as well. 224 African Americans with nondiabetic nephropathy express variants in the gene encoding APOL1. [225][226][227][228][229] Both clinical and experimental studies document the importance of several other genes, especially ones that regulate the podocyte actin cytoskeleton, in modulating the development of proteinuria, foot process effacement, and sclerosis, including RhoA, urokinase receptor, Pdlim2, and connective tissue growth factor.…”
Section: Diseases That Usually Present With Nephrotic Syndromementioning
confidence: 99%
“…Multiple mutations in ACTN4 have been linked to FSGS (19,20). Additionally, ACTN4 deficiency is also found in multiple human primary glomerulopathies, including sporadic FSGS, MCD, and IgA nephropathy (21)(22)(23)(24). However, the molecular mechanisms by which ACTN4 maintains podocytes homeostasis and its biochemical activities remain largely unknown.…”
mentioning
confidence: 99%
“…Before this, animal experiments [64,65] had shown that ACTN4 -absent mice exhibited abundant proteinuria with sclerosis of glomerular capillaries and podocyte foot process effacement, but whether humans were affected in the same way was unknown at that time. In 2011, Liu et al [62] demonstrated that mutations in the non-actin-binding region (e.g., R310Q, Q348R) result in deficiencies of α-actinin-4 and its binding protein CLP36. This disruption of the α-actinin-4-CLP36 complex hinders RhoA signaling and the generation of traction force in podocytes.…”
Section: Actn4 Mutationsmentioning
confidence: 99%
“…Mutations in ACTN4 are related to familial FSGS in an autosomal dominant manner [57,61]. There are two main etiological mechanisms associated with the disorders caused by the mutants: “gain of function” and “loss of function” [62]. Gain-of-function mutations promote actin binding and abnormal aggregation of α-actinin-4 leading to podocyte damage.…”
Section: Actn4 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation